Trends in point‐of‐care ultrasound use among emergency medicine residency programs over a 10‐year period. Issue 2 (30th March 2023) - Gottlieb, Michael; Cooney, Robert; King, Andrew; Mannix, Alexandra; Krzyzaniak, Sara; Jordan, Jaime; Shappell, Eric; Fix, Megan
Abstract: Background: Point‐of‐care ultrasound (POCUS) is increasingly utilized in emergency medicine (EM). While residents are required by the Accreditation Council for General Medical Education to complete a minimum of 150 POCUS examinations before graduation, the distribution of examination types is not well‐described. This study sought to assess the number and distribution of POCUS examinations completed during EM residency training and evaluate trends over time. Methods: This was a 10‐year retrospective review of POCUS examinations across five EM residency programs. The study sites were deliberately selected to represent diversity in program type, program length, and geography. Data from EM residents graduating from 2013 to 2022 were eligible for inclusion. Exclusion criteria were residents in combined training programs, residents who did not complete all training at one institution, and residents who did not have data available. Examination types were identified from the American College of Emergency Physicians guidelines for POCUS. Each site obtained POCUS examination totals for every resident upon graduation. We calculated the mean and 95% confidence interval for each procedure across study years. Results: A total of 535 residents were eligible for inclusion, with 524 (97.9%) meeting all inclusion criteria. The mean number of POCUS examinations per resident increased by 46.9% from 277 in 2013 to 407 in 2022. All examination types had stable or increasing frequency. Focused assessment with sonography in trauma (FAST), cardiac, obstetric/gynecologic, and renal/bladder were performed most frequently. Ocular, deep venous thrombosis, musculoskeletal, skin/soft tissue, thoracic, and cardiac examinations had the largest percentage increase in numbers over the 10‐year period, while bowel and testicular POCUS remained rare. Conclusions: There was an overall increase in the number of POCUS examinations performed by EM residents over the past 10 years, with FAST, cardiac, obstetric/gynecologic, and renal/bladder being the most common examination types. Among less common procedures, increased frequency may be needed to ensure competence and avoid skill decay for those examination types. This information can help inform POCUS training in residency and accreditation requirements.